IMF Staff papers : Volume 8 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1961)
This paper describes and evaluates developments in foreign markets for dollars, sterling, and the major currencies of Western Europe. The most important foreign markets for dollar deposits are in Montreal, Toronto, London, and a number of cities in continental Western Europe. The dollars that are dealt with on external markets may, for purposes of convenience, be treated as if they were handled in two separate ways, though in practice bankers and exchange dealers shift from one way to the other. An owner of dollars may make them available through a financial intermediary, or through a series of financial intermediaries, to someone who wants to borrow dollars. Euro-dollar operations are conducted by banks and financial institutions, and are described in terms of receiving and making dollar deposits. They might equally be described in terms of borrowing and lending dollars. Euro-dollar operations significantly affect the reported ownership of dollar deposits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet